Call for Papers, 11/2 2025: Exploring the Diversity of Representations of Islam in Film and TV Series (Journal for religion, film and media, 2024)
The autumn issue of JRFM 2025 (11/2) examines the diversity of media representations of the rich and varied world of Islamic traditions and practices.